Pengaruh Kualitas Pelayanan dan Customer Retention Terhadap Preferensi Nasabah dalam Menggunakan Jasa Perbankan Syariah dengan Digital Banking debagai Variabel Intervening - Muhammad Kurniawan; Dina Safitri; Dimas Pratomo; Nurlaini Nurlaili (CV. Ulil Albab Corp, 2024)
The aim of this research is to determine the influence of service quality and customer retention on customer preferences with digital banking as an intervening variable. This research uses quantitative methods with a sampling technique, namely incidental sampling. The population in this research are BSI customers. The number of samples taken was 100 respondents. The data analysis methods used are regression analysis and path analysis. The data obtained in this research was then processed using SPSS. The results of this research show that the variables of service quality and customer retention partially have a positive and significant effect on BSI customer preferences. In the variables of service quality and customer retention, service quality does not have a positive and significant effect on digital banking, while customer retention, service quality has a positive and significant effect on digital banking. However, digital banking variables cannot mediate between service quality variables and customer preference variables. Meanwhile, digital banking variables can mediate between customer retention variables and customer preference variables.